New Zealand : 2022 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2022)
New Zealand's management of the pandemic, including health policy and macroeconomic policy support, has been effective in ensuring economic recovery. Output has already recovered to above potential, the labor market is tight, and inflation has risen to above the Reserve Bank of New Zealand's (RBNZ) target range.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; New Zealand